Aplikasi Pemesanan Lapangan Badminton Dengan Fitur Pembayaran Berbasis Android Di Kota Tanjungpinang - Winarni, Ade; Apriyanti, Linda; Pedry, Pedry (LPPM Universitas Putera Batam, 2024)
In the advancing digital era, efficiency and accessibility are increasingly crucial in various fields, including badminton. Badminton attracts individuals from diverse age groups and skill levels, appealing to both men and women. This research aims to design and develop an Android-based badminton court booking application to enhance efficiency and effectiveness in transaction processes at the GOR Kota Tanjungpinang. The software development methodology employed in this research is the Waterfall Method with Unified Modeling Language (UML) system modeling. The Android-based Badminton Court Booking Application is created using TypeScript language with the React Native framework and Firebase as the database platform. The Android-based Badminton Court Booking Application developed using React Native facilitates more responsive and interactive administrative processes and information access. Integrating the application with Firebase as the backend ensures data management reliability and user authentication, storing data in both document and image formats. As a result, the Android-based Badminton Court Booking Application provides more robust validation for managing court booking activities and offers enhanced functionality for users.